Role of isavuconazole in the treatment of invasive fungal infections - Wilson DT; Dimondi VP; Johnson SW; Jones TM; Drew RH (Dove Medical Press, 2016)
Dustin T Wilson,1,2 V Paul Dimondi,1,3 Steven W Johnson,1,4 Travis M Jones,1 Richard H Drew1,5 1Department of Pharmacy Practice, Campbell University College of Pharmacy & Health Sciences, Buies Creek, NC, USA; 2Department of Pharmacy, Duke University Hospital, Durham, NC, USA; 3Department of Pharmacy, Durham VA Medical Center, Durham, NC, USA; 4Department of Pharmacy, Forsyth Medical Center, Winston-Salem, NC, USA; 5Division of Infectious Diseases, Duke University Hospital, Durham, NC, USA Abstract: Despite recent advances in both diagnosis and prevention, the incidence of invasive fungal infections continues to rise. Available antifungal agents to treat invasive fungal infections include polyenes, triazoles, and echinocandins. Unfortunately, individual agents within each class may be limited by spectrum of activity, resistance, lack of oral formulations, significant adverse event profiles, substantial drug–drug interactions, and/or variable pharmacokinetic profiles. Isavuconazole, a second-generation triazole, was approved by the US Food and Drug Administration in March 2015 and the European Medicines Agency in July 2015 for the treatment of adults with invasive aspergillosis (IA) or mucormycosis. Similar to amphotericin B and posaconazole, isavuconazole exhibits a broad spectrum of in vitro activity against yeasts, dimorphic fungi, and molds. Isavuconazole is available in both oral and intravenous formulations, exhibits a favorable safety profile (notably the absence of QTc prolongation), and reduced drug–drug interactions (relative to voriconazole). Phase 3 studies have evaluated the efficacy of isavuconazole in the management of IA, mucormycosis, and invasive candidiasis. Based on the results of these studies, isavuconazole appears to be a viable treatment option for patients with IA as well as those patients with mucormycosis who are not able to tolerate or fail amphotericin B or posaconazole therapy. In contrast, evidence of isavuconazole for invasive candidiasis (relative to comparator agents such as echinocandins) is not as robust. Therefore, isavuconazole use for invasive candidiasis may initially be reserved as a step-down oral option in those patients who cannot receive other azoles due to tolerability or spectrum of activity limitations. Post-marketing surveillance of isavuconazole will be important to better understand the safety and efficacy of this agent, as well as to better define the need for isavuconazole serum concentration monitoring. Keywords: isavuconazole, azole, antifungal, aspergillosis, Mucormycetes, mucormycosis